Operations expenditure modelling of the X-Rotor offshore wind turbine concept. Issue 3 (1st May 2022) - Flannigan, Callum; Carroll, James; Leithead, William
Abstract: O&M of an offshore wind farm is becoming increasingly challenging as farms are being commissioned further from shore. Weather windows are more difficult to navigate leading to longer downtime for turbines. The X-Rotor offshore wind turbine concept directly tackles these O&M challenges by, amongst other advantages, removing the requirements for components that have traditionally contributed high failure rates, repair times and downtimes, and by placing the heavy and expensive machinery closer to sea level. The turbine also benefits from having modular small rotors that can be quickly replaced and repaired onshore, and being able to operate at reduced capacity when there are failures in the modular rotors. This paper presents the StrathX-OM OpEx model. This model features changes to OpEx modelling that will allow for comprehensive analysis of the operations and maintenance costs for a wind farm made up of radical X-Rotor wind turbines with the flexibility to handle changing designs as the technology progresses. The calculation of lifetime O&M costs for a wind farm 100 km from shore showed that the X-Rotor has lower O&M costs than conventional HAWTs for an established design. A sensitivity study on the estimated failure rates of X-Rotor is also presented. This shows that even with significantly over-estimated failure rates the X-Rotor would still be competitive in today's market.